The interactions between ineffective erythropoiesis and ferroptosis in β-thalassemia - Lin, Siyang; Zheng, Yanping; Chen, Meihuan; Xu, Liangpu; Huang, Hailong (Frontiers in Physiology, 2024)
In Guangxi, Hainan, and Fujian Province in southern China, β-thalassemia is a frequent monogenic hereditary disorder that is primarily defined by hemolytic anemia brought on by inefficient erythropoiesis. It has been found that ineffective erythropoiesis in β-thalassemia is closely associated with a high accumulation of Reactive oxygen species, a product of oxidative stress, in erythroid cells. During recent years, ferroptosis is an iron-dependent lipid peroxidation that involves abnormalities in lipid and iron metabolism as well as reactive oxygen species homeostasis. It is a recently identified kind of programmed cell death. β-thalassemia patients experience increased iron release from reticuloendothelial cells and intestinal absorption of iron, ultimately resulting in iron overload. Additionally, the secretion of Hepcidin is inhibited in these patients. What counts is both ineffective erythropoiesis and ferroptosis in β-thalassemia are intricately linked to the iron metabolism and Reactive oxygen species homeostasis. Consequently, to shed further light on the pathophysiology of β-thalassemia and propose fresh ideas for its therapy, this paper reviews ferroptosis, ineffective erythropoiesis, and the way they interact.